Measurements and Knowledge - Montemayor, Carlos (Cosmos and History: The Journal of Natural and Social Philosophy, 2015)
This paper discusses the importance of scientifically informed philosophy and philosophically informed science for improving extant approaches to the study of the mind, and in particular, of conscious awareness. By using the work of Patrick Suppes as an illustration, the paper shows that a balance between science and philosophy is needed not only to produce new insights, but also to prevent dogmatism.